La documentoscopia vial forense y su repercusión en el ámbito del derecho penal: un nuevo esencialismo conceptual de la criminalística - Guillén Pérez, Valentín (Archivos de criminología, seguridad privada y criminalística, 2023)
The functional praxis of documentoscopy encompasses a wide spectrum in the fight against certain criminal networks. Therefore, it is necessary to coin a new scientific term, "road documentoscopy", with the aim of combining knowledge and methods that are sufficiently effective to detect a spurious document, which serves as a prelude to the discovery of other crimes of greater significance: crimes against road safety and crimes involving the illicit trafficking of vehicles. In addition, the professionalisation of road document copying would also lead to a drop in road accident statistics by detecting false documents such as driving licenses and vehicle registrations. Finally, it should be noted that this research work provides practical tools (virtual tools) for operational verification with which it would be possible to detect an apocryphal document in everything related to road transport